Knee kinematics changes with the point of application of the ground reaction force in the medio-lateral direction in simulated Alpine skiing: A pilot studie - Supej, M.; Zorko, M.; Milankovic, L.; Babic, J.; Nemec, B. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of this study was to analyze how the kinematics of the knee joint adapts to the new torque situation when using wider skis in simulated skiing conditions.